Motivations for servitization: the impact of product complexity - Raddats, Chris; Baines, Tim; Burton, Jamie; Story, Vicky Mary; Zolkiewski, Judy (International journal of operations & production management, 2016)
Purpose – The purpose of this paper is to identify the commonalities and differences in manufacturers’ motivations to servitise. Design/methodology/approach – UK study based on interviews with 40 managers in 25 companies in 12 sectors. Using the concept of product complexity, sectors were grouped using the Complex Products and Systems (CoPS) typology: non-complex products, complex products and systems. Findings – Motivations to servitise were categorised as competitive, demand based (i.e. derived from the customer) or economic. Motivations to servitise vary according to product complexity, although cost savings and improved service quality appear important demand-based motivations for all manufacturers. Non-complex product manufacturers also focus on services to help product differentiation. For CoPS manufacturers, both risk reduction and developing a new revenue stream were important motivations. For uniquely complex product manufacturers, stabilising revenue and increased profitability were strong motivations. For uniquely systems manufacturers, customers sought business transformation, whilst new service business models were also identified. Research limitations/implications – Using the CoPS typology, this study delineates motivations to servitise by sector. The findings show varying motivations to servitise as product complexity increases, although some motivational commonality existed across all groups. Manufacturers may have products of differing complexity within their portfolio. To overcome this limitation the unit of analysis was the strategic business unit. Practical implications – Managers can reflect on and benchmark their motivation for, and opportunities from, servitisation, by considering product complexity. Originality/value – The first study to categorise servitisation motivations by product complexity. Identifying that some customers of systems manufacturers seek business transformation through outsourcing.